2018
DOI: 10.1007/s11906-018-0891-x
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene, Genome-Wide Association and Bioinformatic Studies in Pre-eclampsia: a Review

Abstract: It is apparent that different genes show significance in varying populations. Notably, it is reported that apolipoprotein-1 gene polymorphisms are associated with pre-eclampsia development in an African-American population, which may be worthwhile to investigate in a Black South African cohort. Despite the research attention that is focused on this surreptitious syndrome, a definitive cause eludes scientists and physicians, alike. Genetic studies can fulfil a dual purpose of suggesting novel hypotheses through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 110 publications
0
23
0
Order By: Relevance
“…Increasing evidence indicates that the occurrence and development of PE were caused by multivariate interaction including heredity, among which genetic polymorphisms have caught increasingly attention. [ 30 , 31 ] Meanwhile, inflammation is also an accomplice in the development of PE, in which inflammatory factors make a crucial contribution. [ 19 , 32 , 33 ] Considering the importance of inflammation and genetic polymorphisms in the etiology and progression of PE, a growing number of studies have been performed to explore the associations between inflammatory gene polymorphisms and susceptibility to PE.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that the occurrence and development of PE were caused by multivariate interaction including heredity, among which genetic polymorphisms have caught increasingly attention. [ 30 , 31 ] Meanwhile, inflammation is also an accomplice in the development of PE, in which inflammatory factors make a crucial contribution. [ 19 , 32 , 33 ] Considering the importance of inflammation and genetic polymorphisms in the etiology and progression of PE, a growing number of studies have been performed to explore the associations between inflammatory gene polymorphisms and susceptibility to PE.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cell-free DNA testing is an emerging non-invasive alternative to amniocentesis and chorionic villous sampling to detect chromosomal conditions as well as sex chromosomal conditions like Turner and Klinefelter syndrome [34]. Prenatal screening is now expanding to include genetic carrier testing for inheritable diseases, inheritable cancer genetics, and may soon include genes predisposing women to pre-eclampsia [35]. Companies such as Progenity (AscendatMDX) are offering these tests directly to the consumer.…”
Section: Mothermentioning
confidence: 99%
“…However this normal inflammatory response becomes exaggerated in pre‐eclampsia resulting in disruptive activation of monocytes, granulocytes and the endothelium leading to a state of maternal inflammation (Redman and Sargent, 2003). It has been proposed that there may be a genetic susceptibility to inflammation in pre‐eclampsia yet many studies are conflicting (for recent review see (Thakoordeen et al, 2018). A meta‐analysis of maternal polymorphisms in interleukin (IL)‐6 (174 G/C) ( n = 396 pre‐eclampsia and n = 507 normotensive) and tumor necrosis factor (TNF)‐α (308 G/A) ( n = 1888 pre‐eclampsia and n = 2497 normotensive) found that these were not associated with pre‐eclampsia, despite maternal IL‐6 and TNF‐α levels being significantly higher in patients with pre‐eclampsia (Xie et al, 2011).…”
Section: Maternal Inflammation In Pre‐eclampsia: a Potential Role Formentioning
confidence: 99%
“…This suggests that elevations in cytokines may be as a result of the primary pathophysiology. However some subsequent studies have reported opposing findings (Sowmya et al, 2015) and this remains a topic of ongoing investigation (Thakoordeen et al, 2018). However what is clear is that many clinical studies have now reported that women with preeclampsia have increased levels of inflammatory cytokines including IL-6, TNF-α, IL-12 and IL-16, which cause structural and functional changes in endothelial cells, promote the formation of endothelin and reduce acetylcholine induced vasodilatation (Benyo et al, 2001;Fig.…”
Section: Hypertensive Disorders Of Pregnancymentioning
confidence: 99%